Mistakes of Primary School Students: from the Purist Greek to the Native Language - Kολιούση Παναγιώτα; Παπαδοπούλου Σμαράγδα (Education Sciences, 2022)
In the Greek educational reality, the teaching of the linguistic course is accompanied by a peculiarity of the Greek language, which is an alive language that evolves continually and at the same time it draws elements from the past. On the one hand, this double tradition adds to the Greek language verbal wealth, but on the other hand, it constitutes the basic reason for the difficulties the speaker faces while using it. This article focuses on the evolutionary course of the Greek language and the impact of it in the teaching of the linguistic course in order for the archaising elements to survive in the new Greek language. Consequently, the aim of this research is the investigation and the recording of the most usual mistakes that the students of the two last grades of the municipal school do and are connected to the survival of the archaising form of Modern Greek.